2006
DOI: 10.1080/10510970500481672
|View full text |Cite
|
Sign up to set email alerts
|

Framing the Work of Art: Spirituality and Career Discourse in the Nonprofit Arts Sector

Abstract: Based on qualitative data from participant interviews, this study explores how nonprofit arts managers construct the notion of career, and more specifically, how they frame the nature of their work and career choices. Findings revealed that participants employed a spiritual framework of calling, service, sacrifice, and personal rewards to socially construct, understand, and legitimate their nonprofit careers. These framing devices provided the language for participants to make sense of their career decisions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…In addition to the moderators we discussed, it seems sensible to also analyze the (moderating) effects of the type of the organization (e.g. religious/non-religious; profit/non-profit; Smith et al, 2006), the size of the organization (Lynn et al, 2010) and the type of workplace -for example, in terms of the frequency of social interaction (Davidson and Caddell, 1994). In part because the effects of these moderators are controversial (Lynn et al, 2010), we did not refer to them in our analysis.…”
Section: Limitations and Further Researchmentioning
confidence: 99%
“…In addition to the moderators we discussed, it seems sensible to also analyze the (moderating) effects of the type of the organization (e.g. religious/non-religious; profit/non-profit; Smith et al, 2006), the size of the organization (Lynn et al, 2010) and the type of workplace -for example, in terms of the frequency of social interaction (Davidson and Caddell, 1994). In part because the effects of these moderators are controversial (Lynn et al, 2010), we did not refer to them in our analysis.…”
Section: Limitations and Further Researchmentioning
confidence: 99%
“…Given the strong identification that many nonprofit professionals have with the missions of their organizations and the higher calling of their work (Mize Smith, Arendt, Bezek Lahman, & Duff, 2006), it is important to understand the communicative practices in which nonprofit organizations and their members engage to manage tensions between the market-based and mission-based professional identities. Given the strong identification that many nonprofit professionals have with the missions of their organizations and the higher calling of their work (Mize Smith, Arendt, Bezek Lahman, & Duff, 2006), it is important to understand the communicative practices in which nonprofit organizations and their members engage to manage tensions between the market-based and mission-based professional identities.…”
Section: Theorizing An Organizing Tensionmentioning
confidence: 99%
“…This mirrors much research on FBOs in the United States, which indicates that faith plays an important role in motivating FBO employees and volunteers (Ebaugh, Pipes, Saltzman Chafetz, and Daniels, 2003;Greeley, 1997;Hodgkinson, 1990;Hodgkinson, Weitzman, and Kirsch, 1990;Lam, 2002). Interestingly, this spiritual draw to work for an NGO was also present among secular NGO employees, a phenomenon that is discussed in the literature on spirituality in nonreligious workplaces (Ashmos and Duchon, 2000;Buzzanell, 2001;Dawson, 2005;Fox, 1994;Hall, 2002;Lips-Wiersma, 2002;Pokora, 2001;Smith and others, 2006). This pattern among secular NGO staff is not reflected in Table 2 because the table refers specifically to staff members' self-described religious calling to work for an NGO that was associated with membership in and commitment to a specific religion or faith; in contrast, secular NGO workers who discussed being called to NGO work described this calling in broadly spiritual terms, not in reference to a specific religion or faith.…”
Section: Spirituality and Religious Beliefmentioning
confidence: 93%
“…In the United States, Light (2002) reports that nonprofit employees are much more likely than employees in the public and private sectors to choose their jobs due to personal interest or spiritual rewards, and the body of literature on the spiritual aspects of career in a variety of organizations is growing (Ashmos and Duchon, 2000;Buzzanell, 2001;Dawson, 2005 Hall, 2002;Lips-Wiersma, 2002;Pokora, 2001). Smith and others (2006) have found that employees of secular nonprofit organizations often frame their careers in spiritual terms as a way of legitimating their career choice in societies that emphasize external rewards such as salary and promotion as criteria for measuring career success. As Onyx and Maclean note (1996, p. 331), "By these criteria, people who work for nonprofit organizations are often seen as having no careers."…”
Section: Spirituality and Religious Beliefmentioning
confidence: 99%